Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 5 - Logarithmic, Exponential, and Other Transcendental Functions - 5.5 Exercises - Page 362: 42


$y'=(6^{-2x})(1-2x \ln 6)$

Work Step by Step

$y=x(6^{-2x})$ $u=x$ $u’=1$ $v=6^{-2x}$ $v’=-2\ln 6 (6^{-2x})$ $y’=u’v+uv’$ $=(1)(6^{-2x})+(x)(-2)(\ln 6)(6^{-2x})$ $=(6^{-2x})(1-2x \ln 6)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.